(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Future research directions for agricultural geography were the subject of discussion in Area in the late 1980s. The ensuing application of political economy thoughts without a doubt restored interest in agricultural research. This paper contends that agricultural geography contains more noteworthy assorted variety than the dominant political economy talk would propose. It reviews ’other’ territories of agricultural research on policy, post-productivism, people, culture and creatures, presenting future suggestions for research. They ought to guarantee that agricultural research continues rejuvenated rather than repetitive into the following thousand years.